2017
DOI: 10.1371/journal.pone.0189900
|View full text |Cite
|
Sign up to set email alerts
|

Racism and health service utilisation: A systematic review and meta-analysis

Abstract: Although racism has been posited as driver of racial/ethnic inequities in healthcare, the relationship between racism and health service use and experience has yet to be systematically reviewed or meta-analysed. This paper presents a systematic review and meta-analysis of quantitative empirical studies that report associations between self-reported racism and various measures of healthcare service utilisation. Data were reviewed and extracted from 83 papers reporting 70 studies. Studies included 250,850 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
203
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(227 citation statements)
references
References 111 publications
10
203
1
3
Order By: Relevance
“…While we cannot rule out the potential for reverse causality with this cross‐sectional design, there is little support for reverse causality when considering these findings in the context of the wider literature on racism and health. This is the case for studies looking at healthcare experiences/quality outcomes 9 as well as the wider literature on racism as a health determinant 2 . A recent meta‐analysis on experience of racism and health outcomes showed that in studies on experience of racism and mental health, cross‐sectional study designs tended to demonstrate stronger associations with negative mental health measures than longitudinal study designs, although this did not apply to all types of mental health measures 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While we cannot rule out the potential for reverse causality with this cross‐sectional design, there is little support for reverse causality when considering these findings in the context of the wider literature on racism and health. This is the case for studies looking at healthcare experiences/quality outcomes 9 as well as the wider literature on racism as a health determinant 2 . A recent meta‐analysis on experience of racism and health outcomes showed that in studies on experience of racism and mental health, cross‐sectional study designs tended to demonstrate stronger associations with negative mental health measures than longitudinal study designs, although this did not apply to all types of mental health measures 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study it would underestimate the association with unmet need and overestimate the association with satisfaction. Similarly, the validity of self‐reported outcome measures of healthcare such as reported satisfaction and unmet need could be strengthened in future research in New Zealand through the objective measurement of outcomes from actual healthcare encounters, 41 and the use of recorded health data for measures of quality of healthcare such as appropriate and timely treatment and management of health problems 9 . These studies would require substantially different study designs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, physicians can write "prescriptions" for healthy food (with an accompanying voucher or coupon) at a neighborhood Farmer's Market or a participating Walgreens store. [36][37][38][39][40] The many ways that unmet social needs influence the effectiveness of treatments was a key workshop theme. Patients who completed the diabetes education classes were more likely to participate in the community-based programs the team has created (e.g., grocery store tours and community exercise programs) than other patients in the health centers.…”
Section: Box 1 Promising Approaches For Medical and Social Care Intementioning
confidence: 99%